2016
DOI: 10.1002/prep.201500253
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Fast Cook‐Off Simulations

Abstract: Various aspects of fast cook‐off simulations are explored with a spatially one‐dimensional, fully transient numerical model. The model is applied to HMX and consists of equations for the solid (condensed) phase, the gas phase, and the surrounding steel container. The condensed phase HMX decomposition reactions are described by distributed kinetics. The gas phase description includes a detailed chemistry model for the combustion of HMX. Results are presented that outline considerations for simulating fast cook‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The results show that with the increase of heating rate, the ignition time decreases, the ignition position moves to the edge, and the ignition temperature changes little. Gross et al [11] found in the cook-off simulation that small changes in the hot path during fast cook-off would significantly change the predicted ignition time of fast cook-off, but not for slow cook-off. Hobbs et al [12][13] established and verified the cook-off model of fused cast explosive Comp-B3 through ventilation and closed cook-off experiments, and also found that melting is very important in the rapid cook-off process of CL-20.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that with the increase of heating rate, the ignition time decreases, the ignition position moves to the edge, and the ignition temperature changes little. Gross et al [11] found in the cook-off simulation that small changes in the hot path during fast cook-off would significantly change the predicted ignition time of fast cook-off, but not for slow cook-off. Hobbs et al [12][13] established and verified the cook-off model of fused cast explosive Comp-B3 through ventilation and closed cook-off experiments, and also found that melting is very important in the rapid cook-off process of CL-20.…”
Section: Introductionmentioning
confidence: 99%